If approach to innovations differs in locally and foreign owned firms: Case of Lithuania - Tvaronavičienė, Manuela; Degutis, Mantas (Journal of Business Economics and Management, 2007)
Presented paper aims to reveal differences, if any, in innovative behavior of business firms containing foreign and not foreign capital. Innovative behavior in that case is being characterized by scale of investment into research and development, self‐financing pattern and business strategy undertaken by various firms. Juxtaposition of business firms operating in the same economy field but having different ownership origin ‐ local and containing foreign capital ‐ has been performed. Results let us identify differences in approach to innovative activity stipulated by presence of foreign capital. Tendencies obtained in Lithuania plausibly might have been verified in other less advanced European countries in order to check if a consistent pattern could be admitted.First Published Online: 14 Oct 2010